Update of the systematic review of palliative radiation therapy fractionation for bone metastases. Issue 3 (March 2018) - Rich, Shayna E.; Chow, Ronald; Raman, Srinivas; Liang Zeng, K.; Lutz, Stephen; Lam, Henry; Silva, Maurício F.; Chow, Edward
Abstract: Purpose: Radiation therapy is an effective modality for pain management of symptomatic bone metastases. We update the previous meta-analyses of randomized trials comparing single fraction to multiple fractions of radiation therapy in patients with uncomplicated bone metastases. Methods: A literature search was conducted in Ovid Medline, Embase, and Cochrane Central Register. Ten new randomized trials were identified since 2010, five with adequate and appropriate data for inclusion, resulting in a total of 29 trials that were analyzed. Forest plots based on each study's odds ratios were computed using a random effects model and the Mantel–Haenszel statistic. Results: In intention-to-treat analysis, the overall response rate was similar in patients for single fraction treatments (61%; 1867/3059) and those for multiple fraction treatments (62%; 1890/3040). Similarly, complete response rates were nearly identical in both groups (23% vs 24%, respectively). Re-treatment was significantly more frequent in the single fraction treatment arm, with 20% receiving additional treatment to the same site versus 8% in the multiple fraction treatment arm ( p  < 0.01). No significant difference was seen in the risk of pathological fracture at the treatment site, rate of spinal cord compression at the index site, or in the rate of acute toxicity. Conclusion: Single fraction and multiple fraction radiation treatment regimens continue to demonstrate similar outcomes in pain control and toxicities, but re-treatment is more common for single fraction treatment patients.